2015
DOI: 10.1016/j.apjtb.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of toxigenic Bacillus cereus in food and infant feces

Abstract: Objective: To investigate the true incidence of Bacillus cereus (B. cereus) in food and children diarrhea cases. Methods: A total of 110 samples of various dairy products such as raw milk, long life pasteurized milk, yoghurt and infant powdered milk formulas, raw rice, and feces were examined for the presence of B. cereus by selective plating on mannitol-egg-yolkpolymyxin agar. Confirmation of B. cereus was carried out by biochemical tests and PCR. Identification of non-B. cereus isolates was carried out by 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
2
23
0
2
Order By: Relevance
“…This high resistance pattern could be due to irrational and widespread use of few antimicrobials. Agreeably, Organji et al (2015) from Egypt reported that 100% of tested isolates showed resistance to Penicillin G. Moreover, concurring the present finding, Organji et al (2015) reported that, 100% of tested isolates were susceptible to Erythromycin and Vancomycin.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This high resistance pattern could be due to irrational and widespread use of few antimicrobials. Agreeably, Organji et al (2015) from Egypt reported that 100% of tested isolates showed resistance to Penicillin G. Moreover, concurring the present finding, Organji et al (2015) reported that, 100% of tested isolates were susceptible to Erythromycin and Vancomycin.…”
Section: Discussionsupporting
confidence: 76%
“…The overall prevalence of B. cereus in raw bulk milk in Haramaya district was 38.8%. In their study Organji et al (2015) reported far higher prevalence (66.6%) of B. cereus isolated from of raw milk samples in Egypt. This variation could be due to the small sample size examined by the researchers.…”
Section: Discussionmentioning
confidence: 99%
“…All the tested isolates were resistant to penicillin G, whereas sensitive to oxacillin, clindamycin, vancomycin, erythromycin, gentamicin, ciprofloxacin, and ceftriaxone. The data obtained herein with the others (Fenselau et al, 2008;Organji et al, 2015;Jawad et al, 2016) showed that B. cereus has a broad range of antibiotic susceptibility and validate the resistance to penicillin G by comparing to susceptibility to clindamycin, vancomycin, and erythromycin. Conclusion From the obtained data, many conclusions could be drawn, contamination of beef products with B. cereus increase the potential of foodborne infections among the consumers.…”
Section: Http://wwwopenveterinaryjournalcom R Shawish and R Tarabeesmentioning
confidence: 61%
“…cereus is undervalued as a foodborne pathogen, despite the fact that, it has been implicated in various foodborne outbreaks worldwide (Bennett et al, 2013) and this could be attributed to the lack of effective surveillance, underreporting of B. cereus linked food poisoning, and cases of B. cereus food poisoning apparently confused with Staphylococcus aureus and Clostridium perfringens food poisoning due to comparable symptoms (Fricker et al, 2007;StenforsArnesen et al, 2008), finally, B. cereus is not taken in account when diarrhea cases are diagnosed even if the fecal samples gave negative results for the presence of Salmonella, Shigella and Entamoeba in the middle east (Organji et al, 2015).…”
Section: Introductionmentioning
confidence: 99%